2020
DOI: 10.1590/1518-8345.3092.3337
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in the red blood cells obtained from the cell saver in patients submitted to heart surgery

Abstract: Objective: to determine the microbiological characteristics of the red blood cells obtained with the cell saver in heart surgery patients on an extra-body circuit. Method: a cross-sectional and descriptive study conducted with 358 patients scheduled for heart surgery where the saver was used. Sociodemographic variables were collected, as well as from the saver and of the microbial identification in the re-infusion bag proceeding from the cell saver. Informed consent performed. Results: of the 170 GRAM+ bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…S. epidermidis was previously reported to be associated with 69% of culture (+) in sRBCs following the CS-mediated washing of salvaged blood for patients undergoing cardiac surgery. But it did not demonstrate the effect on patients after surgery (5). In contrast, the present results offer insight into postoperative infection incidence in patients that were transfused with bacterially positive sRBCs.…”
Section: Postoperative Infectionscontrasting
confidence: 92%
See 3 more Smart Citations
“…S. epidermidis was previously reported to be associated with 69% of culture (+) in sRBCs following the CS-mediated washing of salvaged blood for patients undergoing cardiac surgery. But it did not demonstrate the effect on patients after surgery (5). In contrast, the present results offer insight into postoperative infection incidence in patients that were transfused with bacterially positive sRBCs.…”
Section: Postoperative Infectionscontrasting
confidence: 92%
“…Previous reports have explored risk factors associated with culture (+) in sRBCs, yielding varying outcomes that may be attributable to differences in patients, exposure time, intraoperative procedures, and the surgical environment (including operating room cleanliness). One study of cardiac surgery patients found that those with a BMI ≥25 who underwent valvular surgery tended to be more susceptible to S. epidermidis cultures (+) in sRBCs ( 5 ). Another controlled study compared new and old operating rooms and detected fivefold lower bacterial counts in sRBCs samples prepared in the new operating room relative to the old room, indicating that operating room cleanliness is likely to impact bacterial deposition ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concern regarding findings of bacteremia in the red blood cells (RBCs) of cell saver blood in adults undergoing cardiac surgery has raised concerns regarding safety of its infusion (19). Bacterial culture growth demonstrated in 60-85% of salvaged blood, attributed to airborne bacteria in the environment, has not been directly correlated with postoperative infections (20).…”
mentioning
confidence: 99%